The Effect of MSCs Derived from the Human Umbilical Cord Transduced by Fibroblast Growth Factor-20 on Parkinson's Disease - Li Jinfeng; Wang Yunliang; Liu Xinshan; Wang Shanshan; Xu Chunyang; Xue Peng; Yang Xiaopeng; Xu Zhixiu; Yin Honglei; Cao Xia; Duan Haifeng; Cao Bingzhen (Hindawi Limited, 2016)
Cell therapy is a potential therapeutic approach for Parkinson's disease (PD). Mesenchymal stem cells derived from the human umbilical cord (hUC-MSCs) give priority to PD patients because of multiple advantages. The appropriate gene transduction of hUC-MSC before transplantation is a promising procedure for cell therapy. Fibroblast growth factor-20 (FGF-20) has been shown to protect dopaminergic neurons against a range of toxic insults in vitro. In this study, the hUC-MSCs were gene transduced with FGF-20, and then we transplanted them into the PD mice model. The results showed that MSC-FGF-20 treatment obviously improved the behavior of PD, accompanied by the increase of tyrosine carboxylase- (TH-) positive cell and dopamine (DA). Furtherly, immunohistochemistry disclosed that MSC-FGF-20 obviously promoted the degradation of nuclear factor-κB (NF-κB), a transcription factor that controls genes encoding proinflammatory cytokines, highly expressed in the nigrostriatal dopaminergic regions in PD patients. Therefore, MSC-FGF-20 has a potential for improving PD, closely related to the degradation of NF-κB.